Life Satisfaction and Pessimism in HIV Positive People - Stanley, Selwyn (International Journal of Psychosocial Rehabilitation, 2014)
The manifestation of negative psychological states has been a recurrent theme in the HIV literature. This study explored the life satisfaction of HIV positive persons in India along with the extent of hopelessness (pessimism) manifested in them.HIV positive adults (N=309), registered with Network for Positive People a NGO in Tamilnadu, India constituted the re- spondents for this investigation. They were administered the Hopelessness Scale (Beck et al., 1974) and the Satisfaction with Life Scale (Diener, 1985). Respondents were compared on the basis of gender and marital status. Data analysis re- vealed that female respondents and those who were ‘single’ showed a significant difference from male respondents and those married and scored higher on pessimism and lower on life satisfaction. Further, the life satisfaction score showed highly significant negative correlations with the overall hopelessness score and its sub-dimensions. These findings are in consonance with the Western literature and show poorer emotional states in HIV positive persons from India and indicate areas for intervention which merit attention.